Objectification or experience? A critical examination of fundamental pedagogical categories in digital health education - Sebastian Ruin (Bern Open Publishing, 2024)
The increasing use of digital media and technologies in sports pedagogical settings comes along with fundamental changes in basic sports pedagogical categories such as body, movement, and experience (Ruin & Giese, 2023). In health education in particular, digital devices are playing a growingly important role (McCall et al., 2018). Thereby digitalisation offers multi-layered and sometimes paradoxical opportunities and risks for health education. On the one hand, tools can help people to actively look after their own health by providing them with differentiated information about their bodies, for example. On the other hand, the information provided by such tools is always pre-formatted, limited to certain factors, subject to measurement errors and mostly geared towards young, healthy and trained men and therefore not very sensitive to the specific concerns of other groups of people. To date these opportunities and risks have not been sufficiently discussed from a sports pedagogical perspective. To gain a deeper understanding of these changes, in this theoretical contribution the mechanisms, opportunities and challenges created by digital health education in physical education are examined with a focus on the use of tools such as wearables. Based on a Bildung-oriented perspective (Wibowo et al. 2023) the possibilities and limits for digital health education in physical education are examined in a first step at the surface level, before a deeper investigation of body, movement, and experience in a digitalised world is undertaken. Bildung-theory serves as a critical background for assessing the (in)appropriateness of pedagogical interventions. This enables critical reflection at a structural level. The investigation reveals that the use of digital technologies run the risk of going hand in hand with reductionist images of humankind and a narrow understanding of education. This tends to reduce people to functional objects that are intended to increase their human capital in the interests of society, which is not pedagogically appropriate. At the same time, however, using digital technologies in digital health education opens up opportunities for experiencing differences between supposedly objective and subjective views of one's own body and movement behaviour. This has the potential to lead to Bildung processes in which the relationship between oneself and the world is profoundly questioned. An example of the impetus for such a process could be when two children are doing the same activity and feel quite similar, but notice through a device that their bodies react in noticeably different ways. This opens up new horizons for exploring the complexity of the connections between physical activity, physical reactions and one's own well-being. Exploring such potential of a Bildung oriented digital health education in a differentiated way can be identified as a fundamental future task of sports pedagogy. References McCall, M., Spencer, E., Owen, H., Roberts, N., & Heneghan, C. (2018). Characteristics and efficacy of digital health education: An overview of systematic reviews. Health Education Journal, 77(5), 497-514. https://doi.org/10.1177/0017896918762013 Ruin, S., & Giese, M. (2023). What is real? (Re-)Locating body, movement and experience in an increasingly digitized world. Current Issues in Sport Science, 8(3), Article 002. https://doi.org/10.36950/2023.3ciss002 Wibowo, J., Krieger, C., Gaum, C., & Dyson, B. (2023). Bildung: A German student-centered approach to health and physical education. European Physical Education Review, 29(2), 233-250. https://doi.org/10.1177/1356336X221133060